ORGANIZATION AND DEVELOPMENT OF THE STRATEGIC SYSTEM AT EDUCATIONAL INSTITUTIONS - Nurieva Umida Buribayevna; Alfira Sofia (Galaxy International Interdisciplinary Research Journal, 2023)
The main objective of the research is to identify the qualitative characteristics of the education system and its typical problems, and to identify promising areas for the support and development of public schools in Uzbekistan.